Involvement of endoplasmic reticulum stress and cell death by synthesized Pa-PDT in oral squamous cell carcinoma cells - Hyo-Eun Yoon; Mee-Young Ahn; Yong-Chul Kim; Jung-Hoon Yoon (Elsevier, 2022)
Background/purpose: Photodynamic therapy (PDT) is a therapeutic alternative for malignant tumors that uses a photosensitizer. This study examined whether synthesized Pheophorbide a (Pa) -PDT induced apoptosis and autophagy involving endoplasmic reticulum (ER) stress in oral squamous cell carcinoma (OSCC) cells. Materials and methods: Human OSCC cells were treated with Pa-PDT, and cell proliferation was examined by MTT assay. Apoptosis and autophagy were measured using Western blot analysis. ER stress was examined using RT-PCR and Western blot analysis. In vivo murine OSCC animal model were treated with intratumoral (IT) Pa-PDT, and investigated the therapeutic effect. Results: Pa-PDT significantly inhibited the proliferation of human OSCC cells in a dose-dependent manner. Pa-PDT induced intrinsic apoptotic cell death and also induced autophagy. Pa-PDT induced ER stress which was observed as demonstrated by the up-regulation of the ER stress marker. Inhibition of the ER stress pathway using 4-phenylbutyric acid (PBA) decreased CHOP and induced inhibition of cell deaths. In addition, the inhibition of ER stress enhanced Pa-PDT mediated autophagy. IT Pa-PDT significantly inhibited the tumor growth and induced apoptosis, autophagy and ER stress in vivo OSCC cells transplanted model. Conclusion: This study showed that synthesized Pa-PDT induced ER stress trigger apoptosis and apoptotic cell death pathways in OSCC cells. The inhibition of ER stress declined Pa-PDT mediated cytotoxicity with an increase of autophagy. These results may provide Pa-PDT exerts anti-tumor effects through ER stress pathway in OSCC cells and may provide a basis for developing Pa-PDT targeting ER stress as a therapy for OSCC.